EFFECT OF PROFITABILITY, ECONOMIC VALUE ADDED, AND ASSET GROWTH TO CASH DIVIDEND POLICY - Idris, Agus Zahron; Orlando, Zam Zam; , Andi Desfiandi; Warganegara, Doni Sagitarian; Edwin Mirfazli; Muhammad , Kamaruzzaman (International Journal of Psychosocial Rehabilitation, 2020)
There are several factors that are thought to influence dividends, especially the distribution of cash dividends. One of the factors affecting the distribution of dividends, especially cash dividends, is the company’s financial performance. This study aims to determine the Effect of Profitability, Economic Value Added, and Asset Growth on Cash Dividend Payment Policies. This study uses samples and analyzes the financial statements of manufacturing companies in the period 2013 to 2017. This study uses quantitative and qualitative data with secondary data sources from the Indonesia Stock Exchange. Data has been tested and fulfilled the classic assumption test and suitability test model with adjusted R2 = 33.6%, then carried out research hypothesis testing using multiple linear regression analysis techniques. The results showed that profitability and Economic Value Added have a positive effect on cash dividend payment policy and Asset Growth does not affect the cash dividend payment policy.